The folk-language signs-stylestems in P. Zahrebelnyi’s novel «I, Bohdan» - Голікова, Наталія Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
This article in that vestigates thesemantics and functions of folkloric language aesthetic signs in P. Zahrebelnyi’snovel «I, Bohdan» acquirethe status of contextual stylestems. With reliance on modern methods of studying language units developed in areas linguostylistics, ethnolinguistics, cognitive linguistics, the folk-language polynoms are analyzed as a part of ethnocultural conceptology that in the fiction discourse appear importantindicators of author’s speech thinking.